Sustainable Entrepreneurship and Barriers: A Comparison of Perceived Barriers in Portugal and Slovenia - Santos, Bárbara; Bernardes, Óscar; Amorim, Vanessa; Rua, Orlando Lima (E- Revista de Estudos Interculturais, 2021)
Sustainable entrepreneurship pursues a triple agenda approximate economic, social, and ecological aspirations. We can agree upon the fact that environmental awareness is becoming more and more important on the global market and among people in general. Companies all over the world, have a bigger awareness, addressing more ecological concerns on their products, in order to become greener for consumers. This makes sustainable entrepreneurship an important topic in society and for the economy in general. This article is about sustainable entrepreneurship and the barriers that are connected to it, along with the comparison of two European Union countries, Portugal, and Slovenia, regarding the perceived obstacles and risk for starting a sustainable business. For this, we did use quantitative data from Eurobarometer with the intention to measure how much weight the upcoming entrepreneurship put on the conservation of nature and how much they think about environmental sustainability. We obtained the data that show the level of importance of ecology in business for the entrepreneurs in Portugal, for the ones in Slovenia, and in this case, we can also compare the data with the European Union average.